Vers une tarification équitable de l’assurance ? - Rochet, Jean-Charles (Assurances, 1986)
Towards equitable insurance tariffs – The intensification of competition on insurance markets is giving more and more audience to the principle of premiums personalization. Antagonistic to the traditional principle of risks mutualization, this new trend aims at "equitable" insurance tariffs, i.e. tariffs such that premiums are exactly proportioned to risks. This article is concerned with two questions: 1. Is it possible to design such equitable tariffs, considering the fact that insurers have only incomplete information about the insured? 2. Are equitable tariffs really desirable?